PENGARUH BERKUMUR LARUTAN MADU HUTAN (APIS DORSATA) TERHADAP INDEKS PLAK PADA MAHASISWA TINGKAT 1 JURUSAN KESEHATAN GIGI POLTEKKES KEMENKES MANADO - I Ketut Harapan; Mustapa Bidjuni (Poltekkes Kemenkes Medan, 2024)
Plaque is a soft and sticky layer that sticks to teeth consisting of protein and bacteria. Removing plaque from the surface of the teeth is not only by brushing your teeth, but also by gargling with mouthwash that contains antibacterial substances. Honey is able to stop the development of bacteria in the mouth which causes a reduction in the plaque layer so that it can influence a decrease in the plaque index in a person's mouth. The aim of this research is to determine the effect of gargling forest honey solution (Apis Dorsata) on the plaque index in Level 1 Students of the Department of Dental Health, Health Polytechnic of the Ministry of Health Manado. This research method uses a tru experimental method to determine the influence between variables. This research was carried out on 19-23 May 2023 at the Department of Dental Health, Poltekkes, Ministry of Health, Manado. The total population is 51 people, and the sample is the total population. Sampling was determined based on inclusion and exclusion criteria. So the sample obtained in this research was 50 people. The data obtained was tabulated and analyzed using the paired sample t-test statistical test. And this research instrument uses a diagnostic tool and plaque index assessment format. The results of the study showed that the average before gargling with honey solution was 3.16 and after gargling with honey solution was 1.19, with a difference of 1.97. Based on analysis using the paired sample t-test, it shows that there is a significant difference seen from the p value = 0.000 (0.000 <0.05). This means that gargling with honey solution has an effect on reducing the plaque index.